Genetic Engineering (IntechOpen, 2021)
Genetic engineering has emerged as a prominent and interesting area of life sciences. Although much has been penned to satiate the knowledge of scientists, researchers, faculty members, students, and general readers, none of this compilation covers the theme in totality. Even if it caters to the in-depth knowledge of a few, the subject still has much scope regarding the presentation of the content and creating a drive towards passionate learning and indulgence. This compilation presenting certain topics pertaining to genetic engineering is not only lucid but interesting, thought provoking, and knowledge seeking. The book opens with a chapter on genetic engineering, which tries to unfold manipulation techniques, generating curiosity about the different modus operandi of the technique per se. The gene, molecular machines, vector delivery systems, and their applications are all sewn in an organized pattern to give a glimpse of the importance of this technique and its vast functions. The revolutionary technique of amplifying virtually any sequence of genetic material is presented vividly to gauge the technique and its various versions with respect to its myriad applications. A chapter on genome engineering and xenotransplantation is covered for those who have a penchant for such areas of genetic engineering and human physiology. The fruits of genetic engineering, the much-talked-about therapeutic proteins, have done wonders in treating human maladies. A chapter is included that dwells on the prospects of therapeutic proteins and peptides. Lastly, a chapter on emerging technologies for agriculture using a polymeric nanocomposite-based agriculture delivery system is included to create a subtle diversity. This compilation addresses certain prominent titles of genetic engineering, which is simply the tip of the iceberg and will be helpful in crafting the wisdom of nascent as well as established scientists, research scholars, and all those blessed with logical minds. I hope this book will continue to serve further investigation and novel innovations in the area of genetic engineering.